2002
DOI: 10.1111/j.0014-3820.2002.tb01405.x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Parental Age Effects on the Evolution of Aging

Abstract: Many studies have found that older parents have shorter-lived offspring. However, the evolutionary significance of these findings is poorly understood. We carried out large-scale demographic experiments to examine the direct effect of maternal age and paternal age on offspring aging in inbred and outbred strains of the fruit fly Drosophila melanogaster. We found that the age of mothers and, to a lesser extent, the age of fathers can have a large influence on both offspring longevity and the shape of the age-sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
118
4
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(132 citation statements)
references
References 65 publications
8
118
4
2
Order By: Relevance
“…However, previous studies focused mainly on the effects of maternal and paternal age, age-specific fecundity, and foraging behavior (Ponsonby and Copland, 1998;Priest et al, 2002;Dixon and Agarwala, 2002;Srivastava and Omkar, 2004), and few studies regarding the effects of ageing on the functional response of predatory insect have been published thus far. Ambrose et al (1996) reported a linear relationship between predator (Rhynocoris marginatus F.) (Heteroptera: Reduvidae) age and the number of prey killed.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies focused mainly on the effects of maternal and paternal age, age-specific fecundity, and foraging behavior (Ponsonby and Copland, 1998;Priest et al, 2002;Dixon and Agarwala, 2002;Srivastava and Omkar, 2004), and few studies regarding the effects of ageing on the functional response of predatory insect have been published thus far. Ambrose et al (1996) reported a linear relationship between predator (Rhynocoris marginatus F.) (Heteroptera: Reduvidae) age and the number of prey killed.…”
Section: Discussionmentioning
confidence: 99%
“…In 5 of 6 experimental lines (2 outbred and 4 inbred lines), increasing maternal age corresponded with decreased lifespan of daughters. 83 Additional experiments also found that increasing parental age (both male and female) corresponded with decreased adult offspring longevity. 84,85 Older females also have offspring with decreased developmental stability, as reflected in increased asymmetry in sterno-pleural chaeta number, which corresponds with decreased offspring viability and longevity.…”
Section: Fertilitymentioning
confidence: 93%
“…Preliminary observations suggest an increased frequency of thin and otherwise abnormal eggshells during aging (unpublished data). Defects in either germ-line or somatic stem cells could contribute to the observed declines in viability of eggs and progeny from old females (Kern et al 2001;Priest et al 2002).…”
Section: Future Directionsmentioning
confidence: 99%